2018
DOI: 10.3390/md16010017
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Uptake of Tetrodotoxin and Saxitoxins into Liver Tissue Slices among Pufferfish, Boxfish and Porcupinefish

Abstract: Although pufferfish of the family Tetraodontidae contain high levels of tetrodotoxin (TTX) mainly in the liver, some species of pufferfish, boxfish of the family Ostraciidae, and porcupinefish of the family Diodontidae do not. To clarify the mechanisms, uptake of TTX and saxitoxins (STXs) into liver tissue slices of pufferfish, boxfish and porcupinefish was examined. Liver tissue slices of the pufferfish (toxic species Takifugu rubripes and non-toxic species Lagocephalus spadiceus, L. cheesemanii and Sphoeroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…It remains unclear whether such specific analogue localization is associated with different toxin absorptions due to differences in physicochemical properties or to the possible existence of an additional TTXs transfer mechanism, selectively acting towards certain analogues. Confirmation of a specific TTX transport mechanism was shown in toxic and conditionally toxic puffer fish in an in vitro experiment which incubated fish liver tissue slices in a toxin solution [24,25]. It was supposed that TTX was transported across the cell membrane of puffer fish liver cells using a carrier-mediated transport system [24].…”
Section: Discussionmentioning
confidence: 89%
“…It remains unclear whether such specific analogue localization is associated with different toxin absorptions due to differences in physicochemical properties or to the possible existence of an additional TTXs transfer mechanism, selectively acting towards certain analogues. Confirmation of a specific TTX transport mechanism was shown in toxic and conditionally toxic puffer fish in an in vitro experiment which incubated fish liver tissue slices in a toxin solution [24,25]. It was supposed that TTX was transported across the cell membrane of puffer fish liver cells using a carrier-mediated transport system [24].…”
Section: Discussionmentioning
confidence: 89%
“…Some species of pufferfish, including S. pachygaster, are known to be non-toxic (Tani, 1945;Jeong et al, 1994). A study shows that S. pachygaster can accumulate TTX if incubated with it for a long time (Nagashima et al, 2018). Since it is known that TTX is transferred to pufferfish through the food chain (Bane et al, 2014), it would be more accurate to say that S. pachygaster can accommodate TTX in favorable conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why such a phenomenon occurs, but it may be that TTX/STXs are selectively taken up by the tissues. Nagashima et al [ 44 ] used an in vitro tissue slice incubation method and found that unlike general marine fish, liver slices of Takifugu rubripes and marine pufferfish of the genus Lagocephalus remarkably take up TTX, but, like general marine fish, hardly take up STXs. The tissue slice incubation method can be applied to other tissues such as the skin and intestine [ 45 ], and we plan to use this method to examine the toxin uptake ability or toxin selectivity of each tissue of C. valentini .…”
Section: Discussionmentioning
confidence: 99%